Analysis of Factor Causing Nomophobia in Adolescents: A Meta- Analysis Study - Rahmah, Aisya Alifa; Mustikawati, Irma Finurina; Septianawati, Paramita; Immanuel, Glorio (Syntax Corporation Indonesia, 2024)
This study aims to provide more in-depth knowledge of the underlying reasons, possible risk factors, and protective variables associated with nomophobia in this demographic group by combining data from various studies. The word “nomophobia” describes a group of actions or symptoms associated with smartphone use. It is considered a contemporary phobia caused by society's interaction with mobile information and communication technology, especially cell phones. Nomophobia, the fear or worry that arises when someone is separated from their smartphone, has become a problem in today's digitally connected culture. This research uses meta-analysis research methods. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) were used in this study. Studies published between 2013 and 2023 were the focus of the search. Factors that influence nomophobia include Duration of Smartphone Use, Dependence on Social Media and the Internet, Compulsive and Obsessive Behavior, Social Relationships and Mental Health, Mindfulness, and Demographic Factors such as gender, employment status, parental education, and level of education. The results of this search provide in-depth information about the characteristics and causes of nomophobia, highlighting the need for focused treatment and support networks to address this increasing problem among adolescents. This meta-analysis seeks to close this gap by methodically investigating the elements that lead to adolescent nomophobia.